THE EFFECT OF LEARNING INTERACTION ON ENGLISH LEARNING PERFORMANCE IN ONLINE PEDAGOGY (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
In the last few decades, innovations have been integrated into education and transformed the context of teaching and studying through rapidly accessible resources, the internet, online learning environments and sharing tools. Because of the prevalent Coronavirus disease in 2019, many people could not attend schools, universities or other structured schooling. Since then, all face-to-face tasks have been interrupted and undertaken at home to prevent social interaction. This condition has an impact on the change to online pedagogy in the Indonesian education system. Studies have shown influential factors in online pedagogy. However, there seems to be insufficient research that exposes other variables in online pedagogy, such as learning interaction and English learning performance. This research discusses the gap and reflects a seminal study that exposes the relationship between learning interaction and English learning performance in online pedagogy in the context of Indonesia. We designed this research quantitatively to test the research model empirically. A web-based survey was used to collect relevant data. The participants were 34 English students at one of the private universities in Indonesia. The findings revealed that students' learning interaction was positively and significantly related to English learning performance in online pedagogy. The research findings implied that interaction among students and their classmates or teacher was a factor determining the success of English language teaching in online pedagogy. The teacher should be aware of how students interact because it would impact their English learning performance.